Optimising the implementation of advance care planning in heart failure - Schichtel, M (2017)
Clinicians are hesitant to talk to patients suffering from heart failure about their care preferences should they become seriously ill. Similarly, patients suffering from heart failure lack the tools to help them identify their care needs and communicate these to their healthcare professionals. This process is also known as advance care planning (ACP). Some studies show that ACP can improve the quality of life in life-threatening illnesses like heart failure. Patients expect their clinicians to initiate conversations about ACP. But as a result of clinicians’ hesitance, ACP rarely takes place and patient care is affected. The overall aim of this thesis is to develop a behaviourally informed intervention targeting clinicians to engage with ACP for patients suffering from heart failure. The different stages of the project were informed by the Medical Research Council’s framework for the development and evaluation of complex interventions. The early development phase of the intervention started with an exploration of the evidence base for the impact of ACP on heart failure. The literature suggested that this led to an improved quality of life, better patient satisfaction with end-of-life care and an improved quality of communication between clinicians and patients. This was followed by a component analysis to identify interventions which had the greatest potential in changing clinicians’ behaviour to engage with ACP. Patient-mediated interventions, reminders systems, educational meetings and academic detailing were among the most promising intervention categories. A subsequent literature review analysed the barriers and facilitators for ACP in heart failure leading to the design of an early model of the intervention. Findings from a clinician interview series advanced the early model and shaped the prototype of the intervention based on the Theoretical Domains Framework and Behaviour Change Techniques. The findings from a focus group study including patients and carers refined the final version of the intervention consisting of: 1. A patient-led Question Prompt List 2. A shared decision-making tool in the form of a Choices of Care Table 3. A clinician-owned ACP Reminder Sheet 4. An ACP Practice-Based Training Session A detailed protocol for a feasibility cluster randomised controlled trial was developed to address issues surrounding the feasibility and acceptability of delivering the intervention in clinical practice. Finally, the results from this thesis informed a model for the involvement of the intervention in the clinical management of heart failure.